2021
DOI: 10.31817/vjas.2021.4.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity Stress on the Growth, Physiology, and Yield of Soybean (Glycine max (L.) Merrill)

Abstract: This study was conducted to evaluate the salt tolerance ability of two soybean cultivars under salinity conditions using a selection of growth and physiological parameters. Three weeks after germination, plants began being treated with either a 100 mM concentration of NaCl in Hoagland solution or a non-salinity (0 mM NaCl) solution. The results showed that the plant height, number of leaves, leaf area index, and shoot and root biomasses were significantly reduced under salt conditions. A similar tendency was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Amino acids can be used as neutralizing compounds against stress conditions, and as a useful strategy to mitigate salt stress, as the foliar spraying of arginine leads to protective effects on plants in alleviating salinity stress by both improving vegetative growth qualities, and improving the enzymatic activities of antioxidant enzymes.s Catalase, Peroxidase, Superoxide Dismutase, and Ascorbate Peroxidase 59,60 , and the increase in phenolic substances and osmotic modification, which lead to a better antioxidant defense system for the plant and osmolytes accumulation 44,61 . When using arginine, the pigments of photosynthesis increased significantly in plants treated with arginine under salinity stress, and thus the efficiency of the photosynthesis process increased, as a result, carbohydrates accumulated, which formed the basic framework for the plants 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids can be used as neutralizing compounds against stress conditions, and as a useful strategy to mitigate salt stress, as the foliar spraying of arginine leads to protective effects on plants in alleviating salinity stress by both improving vegetative growth qualities, and improving the enzymatic activities of antioxidant enzymes.s Catalase, Peroxidase, Superoxide Dismutase, and Ascorbate Peroxidase 59,60 , and the increase in phenolic substances and osmotic modification, which lead to a better antioxidant defense system for the plant and osmolytes accumulation 44,61 . When using arginine, the pigments of photosynthesis increased significantly in plants treated with arginine under salinity stress, and thus the efficiency of the photosynthesis process increased, as a result, carbohydrates accumulated, which formed the basic framework for the plants 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed a reduction in germination percentage with increasing salinity levels, with Lee being the most tolerant and Clark 63 the most susceptible cultivar. Similarly, research on D8 and D140 cultivars indicated a reduction in plant height, number of leaves, leaf area index, and shoot and root biomass after 100 millimolar (mM) NaCl treatment, identifying D140 as having better salt tolerance at 100 mM NaCl concentration (Linh et al 2021). Many of the earlier research studies have examined the salinity tolerance of soybean genotypes during the germination stage.…”
Section: Introductionmentioning
confidence: 96%